Measuring Social Exclusion in Australia: Assessing Existing Data Sources - Wilkins, R; Scutella, A (My University, 2010)
This multidimensionality poses a number of challenges for those that are interested in measuring the extent of exclusion in society. The focus solely on income in the past not only reflected the view that this was the best indicator of the resources available to an individual, but also the practical consideration that it is typically easier to obtain household income information than information on other types of resources, or indeed on other (non-resource) dimensions of disadvantage. In all developed countries, household income is regularly measured for representative samples of households, whereas most other dimensions are measured infrequently or not at all. Moreover, in the event that information on a dimension is collected, it may not necessarily be collected in conjunction with information on other dimensions, thus making full examination of the nature and extent of the exclusion of individuals and families more difficult to ascertain. However, available data have in most countries grown significantly in recent decades, helping to stimulate further action on producing more satisfactory measures of socio-economic deprivation.
Keywords: Income & Finance -- Poverty and disadvantage; Disadvantage -- Exclusion; Disadvantage; Income, wealth and finances; Income & Finance; Disadvantage; Exclusion; Poverty and disadvantage; Income, wealth and finances